Fruit cluster pruning impacts on yield and quality of three tomato cultivars in an organic high tunnel system - Mitchell, Brian Anthony, author; Uchanski, Mark, advisor; Bartolo, Michael, committee member; Elliott, Adriane, committee member (Colorado State University. Libraries, 2018)
The successful production of high-quality, high-yielding crops is important for fruit and vegetable producers, especially growers who use high tunnels. The valuable space within a high tunnel is well-suited to organic farming and can be used to grow many specialty crops. Fruit load management is practiced in tree fruit production (e.g. apples and peaches), but there is little consensus concerning the effectiveness of fruit cluster pruning on tomato (Solanum lycopersicum) when considering its impact on fruit yield, quality, and marketability. There is also no published research on tomato cluster pruning in certified organic systems or intensively-managed high tunnels (e.g. densely-planted, trellised, vegetatively pruned plants) on the Front Range of Colorado. The objective of this research was to address and add to the present knowledge of production techniques for cultivating indeterminate tomatoes in a high tunnel under intensive organic management. In 2016 and 2017, a randomized complete block design was used to test the effects of cluster pruning within a high tunnel on certified organic land at Colorado State University's Agricultural Research, Development, and Education Center, South (ARDEC S.). Two treatments and three cultivars of tomato were selected for the study; the treatment-cultivar combinations were replicated six times within a high tunnel. The treatments involved reducing fruit loads to three fruits and six fruits per cluster while plants with unpruned clusters, which developed up to ten fruits naturally, served as the control. Tomato cultivars evaluated were 'Cherokee Purple', a widely-studied heirloom, and two hybrids: 'Jet Star' and 'Lola'. Parameters measured included total yield, individual fresh fruit weight, soluble solids content, marketable yield, and non-marketable yield. Averaged over two growing seasons, individual fresh fruit weight increased for both hybrids in the three-fruit treatment, but 'Cherokee Purple' did not respond to the cluster pruning treatments. There was no decrease in total yield between treatments and the unpruned control; however, cultivars performed differently with 'Jet Star' yielding more than the other two cultivars. In a complete analysis, soluble solids content and marketability measurements were more influenced by cultivar than cluster pruning treatments: 'Jet Star' had the highest marketable yields of all cultivars tested, while 'Cherokee Purple' produced larger non-marketable yields. In summary, cluster pruning produced larger organic tomatoes without reducing yield or quality for two of the three cultivars used in the study. Cultivar selection remains one of the largest factors in determining yield, quality, and marketability of a crop.